COMPORTAMIENTO DE OVIPOSICION DE RHAGOLETIS TOMATIS EN TOMATE (.LYCOPERSICUM ESCULENTUM) (DIPTERA: TEPHRITIDAE) - L., D. Frías (Acta Entomológica Chilena, 2022)
In experimental conditions R . to m a tis females visited more frecuently big green unripe fruits of 7 cm diameter than small fruits of 2 cm diameter, nevertheless the females oviposited their eggs more frecuently in the small fruits. Further this experiments showed that R. t o m a t is females do not oviposited in ripe fruits. The pheromone that the female is supposed to deposit in the surface of fruits have a gregarious effect on the oviposition.